Pengaruh Periklanan, Citra Merek Terhadap Keputusan Pembelian Sepeda Motor Honda Vario Fi Di Pematangsiantar - Miranda Saragih, Yulia; Sitinjak, Maria Cosmas Salsa; Juliansyah, Rizky; Siregar, Sonia Arnsiah; Saragih, Liharman (Jurnal Sains dan Teknologi, 2023)
− Motorcycles as one of the automotive industries in Indonesia grew rapidly within seven years after the 1998 monetary crisis. In 2005 the population of motorcycles in Indonesia had exceeded 25 million units, while motorcycle sales data until the end of 2006 showed a relatively slow growth rate. tall. Motorcycles are the prima donna for most Indonesian people. The results of the analysis obtained t values ​​> from t table with a regression coefficient value of 2.624 > 2.009. it can be concluded that the advertising variable (X1) partially influences the purchase decision (Y). Purchase decisions are influenced by advertising by 48.8%, while the remaining 51.2% is explained by other variables not examined. This means that advertising has a positive effect on purchasing decisions for the Honda Vario FI in Pematangsiantar City. Simultaneously testing the variable Advertising and Work brand image on purchasing decisions is carried out by the f test. The test results with the help of SPSS obtained an F value of 33.87 with a significance of 0.000. The F value obtained > 3.20 and supported by a significance value < 0.05 indicates that the two independent variables together have a positive and significant influence on the dependent variable. This is supported by the results of testing the coefficient of determination which shows that the magnitude of the influence of the two variables simultaneously is 48.8% which can explain the employee purchasing decision variable. While the remaining 51.2% is the influence of other variables not examined.